2018
DOI: 10.1245/s10434-018-6829-3
|View full text |Cite
|
Sign up to set email alerts
|

Medullary Thyroid Carcinoma: Do Ultrasonography and F-DOPA-PET-CT Influence the Initial Surgical Strategy?

Abstract: BackgroundAt the time of diagnosis, one-third of medullary thyroid carcinoma (MTC) patients show lymph node (LN) or distant metastasis. A metastasized MTC requires different surgical strategies.ObjectiveThis study aimed to determine the value of ultrasound and [18F]fluoro-dihydroxyphenylalanine positron emission tomography with computed tomography (F-DOPA-PET-CT) in localizing MTC, as well as LN and distant metastasis.MethodsThe study included 50 patients (24 males/26 females) with preoperative ultrasound, F-D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 40 publications
3
18
0
1
Order By: Relevance
“… 36 38 The utility of detecting MTC with 18 F-DOPA PET/CT increases proportionally to increases in basal calcitonin in the context of both initial and recurrent disease. 39 , 40 One study evaluating the utility of F-DOPA PET/CT in patients with persistent or recurrent disease found the sensitivity of the study was markedly improved with a serum calcitonin level greater than 150 pg/mL (sensitivity 91% versus 29%) as the cutoff for imaging for metastatic disease according to 2015 ATA guidelines. 3 , 38 …”
Section: Resultsmentioning
confidence: 99%
“… 36 38 The utility of detecting MTC with 18 F-DOPA PET/CT increases proportionally to increases in basal calcitonin in the context of both initial and recurrent disease. 39 , 40 One study evaluating the utility of F-DOPA PET/CT in patients with persistent or recurrent disease found the sensitivity of the study was markedly improved with a serum calcitonin level greater than 150 pg/mL (sensitivity 91% versus 29%) as the cutoff for imaging for metastatic disease according to 2015 ATA guidelines. 3 , 38 …”
Section: Resultsmentioning
confidence: 99%
“…In a review of 50 patients with elevated serum Ctn, thyroid ultrasound positively identified 90% of patients with malignant nodules compared to F-DOPA-PET-CT imaging correctly identifying 86%, with 14% labeled as false negative. However, F-DOPA-PET-CT imaging correctly identified all patients with distant metastasis [54]. Other reports showed much more limited sensitivity, with a 66% detection rate on a per-patient basis and a 71% detection rate on a perlesion basis in a review of 139 patients with known MTC [59].…”
Section: F-dopa-pet-ct Scanmentioning
confidence: 89%
“…1). Thyroid ultrasound has a reported sensitivity of 90% in identifying a malignant lesion in the correct thyroid lobe, but only 71% sensitivity in localizing microcarcinoma [54]. In a study of 118 patients with MTC, approximately 86% were in middle or upper poles [55].…”
Section: Thyroid Ultrasoundmentioning
confidence: 99%
“…Beim MTC steht mit dem ( 18 F-)DOPA-PET/CT auch eine molekulare Bildgebung zur Verfügung, die bei fortgeschrittener Erkrankung hilfreich sein kann [ 2 ].…”
Section: Schilddrüsentumorenunclassified